Functional Characterization and Toxicity of Pectin from Red Chilto Fruit Waste (Peels) - Orqueda, Maria Eugenia (2023)
Background: Food and agricultural wastes constitute a rich source of functional ingredients for the food, pharmaceutical, and cosmetic industries. In this context, by-products from the red variety of Solanum betaceum fruits (chilto) from Northwestern Argentina are suitable sources for pectin extraction. Methods: In this study, pectin from the peels of red chilto fruits was extracted and characterized. Results: The recovery yield of red chilto peel pectin was about 24%, and it was co-extracted with 40.0 mg phenolic compounds, 6.5 mg anthocyanins, and 4.7 g proteins per 100 g of pectin. The pectin obtained from red chilto showed proper technological functionality displaying water and oil holding capacities of 4.2 and 2.0%, respectively, an emulsifying capacity of 83%, emulsion stability of 87.5%, foaming capacity of 21.1%, and foaming stability of 79.1%. The pectin displayed antioxidant activity with the ability to scavenge ABTS radical, superoxide anion, and H2O2. The polysaccharide exhibited in vitro hypoglycemic potential and inhibited the α-amylase enzyme, retarded glucose diffusion, and improved the cellular uptake of glucose in a Saccharomyces cerevisiae model. The extract was non-toxic on acute toxicity tests. Conclusions: Red chilto pectin showed potential as a new and safe functional ingredient for the design of foods, health products, and cosmetics.